(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article analyses the current state of the country's defence leadership, command, and control system. Based on this research, three possible directions for its optimization have been formulated. The author argues the thesis that increasing the effectiveness of the system for leadership, command, and control of the country's defence is possible through improvement of the legal framework, organizational improvement of the system and technological modernization.